Analisis Perbedaan Bid Ask Spread dan Volatilitas Saham Sebelum dan Sesudah Pengumuman Stock Split - Febrianti, Noerita (BISMA (Bisnis dan Manajemen), 2018)
This study aimed to analyze the differences of bid ask spread and stock volatility before and after the announcement of stock split on companies listed in Indonesia Stock Exchange 2010-2013 period. The samples are 30 companies chosen by purposive sampling method. This study used event period 5 days before and 5 days after stock split with descriptive statistical analysis techniques, the normality test (one sample kolmogorov smirnov test), and hypothesis testing (wilcoxon signed ranks test). The results of the descriptive statistics indicate that the bid ask spread after announcement of stock split has decreased while increasing stock volatility than before announcement. However, the results of hypothesis testing with the wilcoxon signed ranks test showed that both the bid ask spreads and stock volatility is not significant difference between before and after announcement of stock split.